El modelo de gestión de las migraciones en Cataluña: ¿una “vía catalana” de integración? - Solé, Carlota; Parella, Sònia (Política y Sociedad, 2008)
Migratory movements from the rest of Spain were the foundation for Catalonia’s population growth until 70s. In the last years, we assist to the beginning of a new wave of immigration from non communitarian countries, which, far from becoming stable, has increased, diversified and extended throughout the territory. Certainly, the Government of the Generalitat has a long history of developing policies on immigration, with the first Interdepartmental Immigration Plan (1993-2000) in 1993. Nevertheless, the third and last Plan, The Citizenship and Immigration Plan (2005-2008), although it maintains coherence with some of the containts and guidelines of previous plans, it introduces important innovations, as well as a new concept of citizenship based on residence, the incorporation of identity as a criteria to define policies or the definition of areas for priority action. Although this plan has been marked for political uncertainty and it can’t be evaluated yet, in the article we discuss how the principles of the plan want to consolidate the named “catalan way” of integration.
Keywords: Immigration; Government of the Generalitat; Catalonia; Political actions; Citizenship; Identity; Integration